PEMANFAATAN LINGKUNGAN SEKOLAH SEBAGAI SUMBER BELAJAR IPS - Nurlaili Dina Hafni (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2020)
Social studies is a subject that uses an integrated approach that combines four fields of study, namely economics, sociology, geography and history. Integrated learning is intended to provide meaningful experiences to students and in their delivery the teacher chooses a specific theme or topic, this learning approach enables students both individually and in groups to actively seek, explore and discover concepts and principles holistically and authentically. The way the teacher packaging the learning is very influential on the meaningful experience for the students. The surrounding environment as a learning resource is very beneficial for the social studies learning process, this is because the learning resources are close to students, so students are easier in the process of understanding the learning resources. The environment can provide a picture that is holistic and authentic, the condition is very heterogeneous, so it shows a source of learning that requires integration between learning materials. This environmental potential can be in the form of social, economic, cultural and geographic environments. Linking class to the community environment provides many opportunities for students to learn the basic ability to take action in the community in the form of participation.